Tour Guide License to Improve Tourism Human Resources Professionalism in Tana Toraja Regency - Margaretha WR (Universitas Muhammadiyah Gorontalo, 2021)
This study examines the tour guide license in improving the professionalism of tourism human resources in Tana Toraja Regency. A tour guide has a very important license, this license proves the competence of a tour guide so that tourists do not hesitate in using his services. The research method used is descriptive qualitative research methods. Data collection techniques were carried out by means of observation, interviews and documentation. This research was conducted at tourist objects in Tana Toraja Regency and related agencies since July-October 2020. Based on the research results, it was found that currently there are still many illegal tour guides in Tana Toraja Regency who are not licensed, the lack of tour guides' attention to the importance of this license has an impact on the image of tourism in Tana Toraja Regency. The government in this case has made various efforts to improve professional tourism human resources in Tana Toraja district by conducting education and training as well as controlling unlicensed foreign guides by imposing criminal and administrative sanctions. The license also has a validity period of 2 years and has 3 levels, namely Young Tour Guide, Intermediate Tour Guide, and Tour Leader. The license function for tour guides is as legal protection for tour guides in carrying out their profession.